Inhibitors of VPS34 and fatty-acid metabolism suppress SARS-CoV-2 replication - Williams, Caroline G.; Jureka, Alexander S.; Silvas, Jesus A.; Nicolini, Anthony M.; Chvatal, Stacie A.; Carlson-Stevermer, Jared; Oki, Jennifer; Holden, Kevin; Basler, Christopher F. (Cell reports (Cambridge), 2021)
Coronaviruses rely on host membranes for entry, establishment of replication centers, and egress. Compounds targeting cellular membrane biology and lipid biosynthetic pathways have previously shown promise as antivirals and are actively being pursued as treatments for other conditions. Here, we test small molecule inhibitors that target the PI3 kinase VPS34 or fatty acid metabolism for anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) activity. Our studies determine that compounds targeting VPS34 are potent SARS-CoV-2 inhibitors. Mechanistic studies with compounds targeting multiple steps up- and downstream of fatty acid synthase (FASN) identify the importance of triacylglycerol production and protein palmitoylation as requirements for efficient viral RNA synthesis and infectious virus production. Further, FASN knockout results in significantly impaired SARS-CoV-2 replication that can be rescued with fatty acid supplementation. Together, these studies clarify roles for VPS34 and fatty acid metabolism in SARS-CoV-2 replication and identify promising avenues for the development of countermeasures against SARS-CoV-2. [Display omitted] •VPS34 and fatty acid metabolism inhibitors impair SARS-CoV-2 growth•Post-entry steps in the SARS-CoV-2 replication cycle are impaired•The inhibitors alter SARS-CoV2 replication center morphology•Knockout of fatty acid synthase also impairs SARS-CoV-2 growth Williams et al. employ pharmacological inhibitor and genetic knockout approaches to demonstrate critical roles for the class III phosphatidylinositol 3-kinase VPS34 and fatty acid metabolism in SARS-CoV-2 growth. The data further implicate triacylglycerol production and protein palmitoylation as critical functions related to fatty acid metabolism that are needed by SARS-CoV-2.